1903 S.D. Rev. Codes, Penal Code, &sect - (:unkn) unknown (My University, 1903)
Prohibited the carrying of a concealed slungshot, firearm, or sharp or dangerous weapon.
&sect
470-471
Keywords: CARRY - CONCEALED